OUTCOME ANALYSIS OF TWO DIFFERENT INJECTION SOLUTIONS FOR EPIDURAL INJECTION IN RADICULAR LUMBAR BACKACHE SYNDROMES - Saqib, Muhammad; Bhatti, Sajid Nazir; Khan, Muhammad Ayaz; Khan, Muhammad Mukhtar; Afridi, Ehtisham Ahmed Khan; Khan, Rubaiqa; Khan, Muhammad Imran (Journal of Ayub Medical College Abbottabad, 2016)
Background: Backache is a significant source of disability and suffering in our society. The treatment modalities need continued enhancement in order to achieve the desired goals of lowering morbidity and financial losses while improving the response of the patient. Methods: This prospective comparative study was conducted at the department of Orthopaedics and Spine Surgery, Khyber Teaching Hospital Peshawar from July 2013 to June 2015. Two interventional groups were designated; Group 1 was comprised of 54 patients who were injected with epidural bupivacaine plus methylprednisolone while Group 2 included 55 patients who were injected with bupivacaine only. Outcome was assessed using the visual analogue scale and Oswestry disability index (ODI). Results: Fifty-five female and 54 male patients with mean age 49.37 years±10.46 SD, Mean symptoms duration was 15.01 months±9.32 SD. Common presenting symptoms were backache (77.1%), lower limbs pain (66.1%), dermatomal paresthesias (54.1%) and neurogenic claudication in 57.8% patients. The mean visual analogue score (VAS) after injection was 3.18±1.29 while mean ODI after injection was 23.615. There was a statistically significant reduction in VAS scores (2-sided p=0.003, OR =4.03, 95% CI: 1.535-10.60) following the injection. Conclusion: An epidural spinal injection is a viable option for achieving relief of pain & improves functioning in individuals with radicular backache. However, further research is advised in order to clarify the role of ESI for long-term relief. Keywords: Backache, Outcome; Epidural steroid injection; Local anaesthetic